Filsafat Islam pada Masa Golden Age dan Kontribusinya dalam Dunia Pendidikan - Harahap, Hotmasarih; Salminawati, Salminawati; Lubis, Indah Syafiqah; Harahap, Sri Wahyuni (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
This study aims to look at the history of the development of Islamic philosophy which in its time influenced world civilization, to find out the famous Islamic philosophy figures and make a very large contribution to this day, some of the theories put forward by Muslims are still used in the modern era such as the ideas of Ibn Sina on tuberculosis (TBC) and ethanol, Al-Khwarizmi's thoughts on mathematics Al-Gebra, discovering the number zero (0), astronomy and many other meritorious scientists. The research method used in this article is a literature study by digging up information about the Golden Age of Islamic Philosophy from various works of literature such as books, journals, articles, and other scientific papers. The results of this study are in the 9th century to the 12th century Islam developed rapidly and influenced world civilization. The development of Islam succeeded in giving birth to Muslim scholars and competing with the West at that time in the Dark Age phase because it was influenced by Church dogma and the inquisition which slowed down intellectual and technological development. Philosophy greatly influences the world of education. Islamic educational institutions developed rapidly through madrasas and higher education institutions at a time when Europe was experiencing its dark period. Islamic education and science in the Middle Ages were supported by Islamic scholasticism, which tried to reconcile Greco-Hellenistic thought with Islamic religious teachings, which reached its peak during the time of Al-Ghazali, and the impressive progress of Islamic civilization in the Middle Ages through Muslim philosophers such as Al-Kindi, Al-Farabi, Avicenna, Omar Khayyam, and others.